Modeling Apartment Purchase Intention Using The Extended Theory Of Planned Behavior In Dhaka City, Bangladesh - Islam, Muhammad Ariful (2024)
Understanding the factors that influence apartment purchase intention is crucial for real estate companies. This research aimed to identify these factors and their impact on buyers' intentions. To achieve this, a quantitative approach using partial least squares structural equation modeling (PLS-SEM) was employed. To identify the relevant factors, an exploratory factor analysis (EFA) was conducted on a sample of 236 participants in first survey. After revising the questionnaire based on the EFA results, new data were collected from 304 samples in second survey for better result in CFA. The study, rooted in the Theory of Planned Behavior (TPB), considered elements such as perceived physical quality and access to money. These factors, identified through a literature review, were incorporated to a sample size of 304 complete questionnaires. SPSS and SmartPLS 4 software facilitated data analysis. The findings indicated positive effects of independent variables (attitudes, subjective norm, perceived behavioral control, perceived physical quality, and access to money) on apartment purchase intention. The moderation analysis revealed no significant moderating effect of access to money. This study contributes valuable insights by introducing two predictors, perceived physical quality and access to money, to the TPB model in the context of apartment purchases in Dhaka City, Bangladesh's real estate industry.